Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pemanen Di Kebun Tinjowan Regional II PT. Perkebunan Nusantara IV - M. Tegar Maulana; Junaidi (JURNAL AGRICA, 2026)
The plantation industry, as part of the agribusiness sector, plays a vital role in boosting the economy, particularly in the supply of raw materials and the creation of jobs.. Therefore, workplace factors not only affect employee comfort but also influence the company’s overall performance, including the achievement of production targets and business profits. This study was conducted at the Tinjowan Regional II Plantation of PT Perkebunan Nusantara IV.The purpose of this study is to determine the effect of the work environment and work discipline on the performance of harvesters. This study employs a quantitative descriptive approach using Proportionate Stratified Random Sampling, with the sample size determined according to Isaac and Michael at a 10% margin of error, comprising 108 respondents at the Tinjowan Plantation. Data analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Based on the research results, the partial analysis indicates that the Work Environment (X1) does not have a significant effect on employee performance (Y). Meanwhile, the Work Discipline variable (X2) shows a significant effect on the employee performance variable (Y). Meanwhile, the simultaneous test indicates that both variables together (simultaneously) have a significant effect on employee performance (Y).